2017
DOI: 10.1186/s12916-017-0934-1
|View full text |Cite
|
Sign up to set email alerts
|

Towards new recommendations to reduce the burden of alcohol-induced hypertension in the European Union

Abstract: BackgroundHazardous and harmful alcohol use and high blood pressure are central risk factors related to premature non-communicable disease (NCD) mortality worldwide. A reduction in the prevalence of both risk factors has been suggested as a route to reach the global NCD targets. This study aims to highlight that screening and interventions for hypertension and hazardous and harmful alcohol use in primary healthcare can contribute substantially to achieving the NCD targets.MethodsA consensus conference based on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 79 publications
(81 reference statements)
0
11
0
Order By: Relevance
“…Other implications of this research are clear: Alcohol consumption should be assessed at the primary care level whenever there is elevated BP 71. Unfortunately, despite some guidelines recommending such an approach, it is rarely followed in clinical practice (for the example of the 6 largest European Union countries72).…”
Section: Discussionmentioning
confidence: 99%
“…Other implications of this research are clear: Alcohol consumption should be assessed at the primary care level whenever there is elevated BP 71. Unfortunately, despite some guidelines recommending such an approach, it is rarely followed in clinical practice (for the example of the 6 largest European Union countries72).…”
Section: Discussionmentioning
confidence: 99%
“…The deficits identified in this study are worth overcoming, as alcohol screening and brief intervention have showed positive results in many European projects. 25 27 28 Lack of resources, training and support from management, as well as workload 26 have been described as barriers to the adoption of screening and brief intervention. 26 We believe in the importance of finding economically sustainable ways of working against these barriers with the objective of systematising alcohol interventions.…”
Section: Discussionmentioning
confidence: 99%
“…So far, there has been no program for alcohol consumption reduction in Tibet. Experiences from European countries showed that even with the existence of screening and appropriate interventions for hazardous alcohol use and use disorders, a lack in implementing the measures prevented success in non-communicable disease control [35].…”
Section: Discussionmentioning
confidence: 99%